WITNESSES OF DIFFABLE IN COURT BASED ON THE CONCEPT OF AHLIYAH IN ISLAM - Maulana, Diky Faqih; Chabiba, Omiga; Rozak, Abdul (Al-Maslahah : Jurnal Ilmu Syariah, 2023)
This paper discusses the position of disabilities as witnesses in court. Where the requirements for a person to become a legal subject have legal competence and are considered mature. The concept of proficiency in Islam states that disability can be positioned as a barrier to proficiency, but it is different from Indonesian law which states that disability is a legal subject. This research is a qualitative research which is literature study. The results showed that the disability condition does not result in a loss of position as a legal subject as long as it does not involve limitations in testifying in court. Disability witnesses can be accepted if it meets the requirements as a legal subject. Disability witnesses also needs to be adjusted according to their abilities. However, if a doctor or psychiatrist considers matters regarding the weak ability of a person with a disability, the district court has the right to determine a person with a legal disability.